Cena wolności. Agentura SB w Instytucie Germanistyki Uniwersytetu Warszawskiego. Przypadek Karola Sauerlanda - Kunicki, Wojciech (Przegląd Archiwalny Instytutu Pamięci Narodowej, 2023)
The article documents the contacts of the prominent Polish Germanist of Professor Karol Sauerland from the Security Service in the second half of the 70s in Warsaw. Sauerland acted in specific conditions informing the Security Service about the activities of the German and Austrian cultural institutions and diplomatic offices. Was it the price of freedom that this prominent scholar exercised? Did he play a specific game with the Security Service or was he used by them? The author of the article tries to answer these questions.